1982
DOI: 10.1515/zna-1982-0611
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative X-Ray Diffraction Study of Aqueous MnSO4 and Crystals of MnSO4·5H2O

Abstract: X-ray single crystal analysis of MnS04 • 5H2O shows that the manganese atoms are octahedral ly coordinated by oxygen atoms, four of which belong to water molecules and two to sulphate groups.A model derived from the crystal structure was fitted to the X-ray scattering intensities from aqueous MnS04. Good agreement with experimental data is achieved using a model in which Mn(H20)6-2(0S03)z +2 " 2z interacts with about ten water molecules and each sulphate ion with about seven water molecules.Analysis of X-ray [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…First, all the crystal structures in the Cambridge Structural Database (CSD) 88 that contain a hexahydrated Mg 2+ ion have all six water molecules in the inner shell (octahedral coordination) . Second, solutions containing Mg 2+ ions have been widely investigated using X-ray diffraction methods and these experiments have consistently found the inner shell surrounding these ions to contain six water molecules. , ,, Third, computational studies of gas-phase hexahydrated Mg 2+ ions have been reported at several computational levels, ,,, and the global minimum on the potential energy surface (PES) has been identified as Mg[H 2 O] 6 2+ with T h symmetry. In this arrangement, the water dipoles point directly toward the magnesium ion (see Figure ), indicative of a strong metal ion−water dipole interaction that also minimizes the water−water repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…First, all the crystal structures in the Cambridge Structural Database (CSD) 88 that contain a hexahydrated Mg 2+ ion have all six water molecules in the inner shell (octahedral coordination) . Second, solutions containing Mg 2+ ions have been widely investigated using X-ray diffraction methods and these experiments have consistently found the inner shell surrounding these ions to contain six water molecules. , ,, Third, computational studies of gas-phase hexahydrated Mg 2+ ions have been reported at several computational levels, ,,, and the global minimum on the potential energy surface (PES) has been identified as Mg[H 2 O] 6 2+ with T h symmetry. In this arrangement, the water dipoles point directly toward the magnesium ion (see Figure ), indicative of a strong metal ion−water dipole interaction that also minimizes the water−water repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…The development of microporous materials has led to investigations of the factors governing the amine-templated syntheses of metal sulfates (Behera et al, 2004). The present report on a new ammonium manganese sulfate, which was obtained unexpectedly in a hydrothermal synthesis intended for this purpose, is a contribution to the limited number of structural studies of inorganic manganese sulfate compounds, such as, for example, Mn(HSO 4 ) 2 , Mn(HSO 4 ) 2 ÁH 2 O and Mn(HSO 4 ) 2 (H 2 SO 4 ) (Stiewe et al,1998), MnSO 4 ÁH 2 O (Le Fur et al, 1966) (Chang et al, 1983), MnSO 4 Á5H 2 O (Caminiti et al, 1982), MnSO 4 ÁH 2 O (Wildner & Giester, 1991), and MnSO 4 Á4H 2 O (Held & Bohatý, 2002). The sulfatomanganate(II) dianion can exist as a distinct entity, as noted in histidinium tetraaquadisulfatomanganate (Wojtczak & Jaskó lski, 1989) and ethylenediammonium tetraaquadisulfatomanganate (Chaabouni et al, 1996); both salts have monodentate sulfate groups only.…”
Section: Commentmentioning
confidence: 99%